Can alternative wine networks foster sustainable business model innovation and value creation? The case of organic and biodynamic wine in Tuscany - da Rocha Oliveira Teixeira, Raiza; Arcuri, Sabrina; Cavicchi, Alessio; Galli, Francesca; Brunori, Gianluca; Vergamini, Daniele (Frontiers in Sustainable Food Systems, 2023)
Over the past two decades, the wine sector has witnessed a significant rise in sustainable practices driven by concerns about sustainability and their impact on wine quality. However, the lack of a common framework for sustainability concepts has resulted in a wide range of practices. Among these, biodynamic viticulture has gained remarkable traction among producers due to its perception as a strong quality indicator, despite the lack of scientific consensus and regulatory alignment across countries. Biodynamics traces its origins back to the organic movement and is viewed by some scholars as a radical progression of organic agriculture. The surging popularity of biodynamics is rooted in the expanding organic movement, reflecting consumer demand for ecologically-conscious, premium goods. Amid this complex backdrop, the wine industry grapples with navigating diverse sustainability approaches and formulating effective business models for competitiveness. Vital is comprehending and adeptly conveying sustainability values to consumers. Prior research mainly quantified sustainability’s impacts, external drivers, and motivations. However, a gap remains in exploring sustainable business models’ role in driving innovation and value creation through alternative networks in the wine sector. This paper presents findings from a phased qualitative study in Tuscany (Italy), reflecting on the evolving landscape. The results underscore synergies between biodynamic and organic approaches, emphasizing their strong connection with the territory. These strategies synergistically promote sustainability and differentiation, enhancing product quality, reducing environmental impact, and fostering territorial engagement. The study accentuates the role of territorial and business context, profoundly influencing collaborative and proactive strategies among producers, exemplified by networks like Lucca Biodinamica. These networks catalyze innovation, knowledge dissemination, and collaborative initiatives, profoundly impacting strategy adoption and advocating for sustainability. Within such ecosystems, a nurturing environment for sustainability practices is cultivated, spurring innovation and winery cooperation. Case studies vividly illustrate that wineries within these networks frequently adopt proactive sustainability stances, grounded in shared environmental and societal commitment. Conversely, some scenarios feature place-rooted leadership models tied to factors like origin, winemaking tradition, and wine tourism, driving innovation. Participating in alternative wine networks represents a strategic choice with lasting personal and economic implications–a framework for innovation and embracing sustainability.